Deductive Thematic Analysis of Educational Leadership Styles in Indonesian Religious School - Lumban Gaol, Nasib Tua; Lumban Tobing, Lasmaria; Pardede, Vera Winda; Bukidz, Danny Philipe; Sianturi, Murni; Purba, Enricho Fiktorando (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This research aims to reveal the principal leadership styles of Christian religious secondary schools in Indonesia. This study used a qualitative descriptive approach. The informants in the study were teachers, vice principal, and school principal in a Christian religious secondary school. The data was collected through semi-structured interviews. Subsequently, the data was analyzed using deductive thematic analysis, and its validity was checked using triangulation. The study results showed that the principal implemented five leadership styles in a Christian religious secondary school: paternalistic, charismatic, servant, transformational, and autocratic. This study indicates that leadership styles are urgently needed to improve Christian religious education quality; however, they are still limited in the literature. Therefore, the Ministry of Religion Affairs, particularly the Directorate General for Christian Community Guidance, should create a concise policy on leadership competency for Christian religious school principals. Furthermore, each principal in Christian religious schools should carry out various leadership styles properly to enhance management and leadership practices in their educational organizations.